ANALISIS PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP MINAT BELAJAR MATA PELAJARAN MATEMATIKA SISWA SD - Mutiara Diaz Fernanda, Alfina; Dewi Pramesta, Aulia Luthfi; Harsono; Masduki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of using interactive video-based learning media on students' interest in learning mathematics at SDN Wonokerto 1. This study used a quasi-experimental design with two groups: an experimental group that used video media and a control group that used conventional learning methods. Data were collected through pretest and posttest questionnaires to measure students' interest in learning, which were then analyzed using a paired t-test. The results showed that there was no significant difference between the experimental and control groups, both in the pretest (t(23) = 0.200, p = 0.844) and posttest (t(23) = 0.268, p = 0.791) scores. Although there was a slight increase in learning interest in both groups, the use of video-based learning media did not have a significant impact on students' interest in learning mathematics. These results indicate that other factors such as students' internal motivation, teacher readiness, and duration of video media use need to be considered in order for this media to have a greater impact on learning.